Local woman missing eaudiobook - Kubica, Mary (2021)
New York Times Bestseller "Dark and twisty, with white-knuckle tension and jaw-dropping surprises." —Riley Sager, New York Times bestselling author of Home Before Dark In this smart and chilling thriller, master of suspense Mary Kubica, author of Just the Nicest Couple, takes domestic secrets to a whole new level, showing that some people will stop at nothing to keep the truth buried. People don't just disappear without a trace... Shelby Tebow is the first to go missing. Not long after, Meredith Dickey and her six-year-old daughter, Delilah, vanish just blocks away from where Shelby was last seen, striking fear into their once-peaceful community. Are these incidents connected? After an elusive search that yields more questions than answers, the case eventually goes cold. Now, eleven years later, Delilah shockingly returns. Everyone wants to know what happened to her, but no one is prepared for what they'll find... Don't miss Mary Kubica's chilling upcoming novel, She's Not Sorry, where an ICU nurse accidentally uncovers a patient's frightening past... Look for these other edge-of-your-seat thrillers by New York Times bestselling author Mary Kubica: The Good Girl Pretty Baby Don't You Cry Every Last Lie When the Lights Go Out The Other Mrs. Just The Nicest Couple She's Not Sorry